The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0891-5849(00)00516-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood glutathione redox status in gestational hypertension

Abstract: Abstract-Gestational hypertension during the third trimester reflects an exaggerated maternal inflammatory response to pregnancy. We hypothesized that oxidative stress present even in normal pregnancy becomes uncompensated in hypertensive patients. A glucose-6-phosphate dehydrogenase (G6PD) activity sufficient to meet the increased reductive equivalent need of the cells is indispensable for defense against oxidative stress. The erythrocyte glutathione redox system was studied, where G6PD is the only NADPH sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…The reports on GSH concentrations during pregnancy are also controversial: some investigators showed an increase (Németh et al 2001;Wisdom et al 1991), whereas others reported a decrease (Arikan et al 2001) or no significant change (Naziroglu et al 2004) during pregnancy. Németh et al (2001) suggested that an increased GSH concentration in pregnant women was an adaptation to maintain the adequate redox milieu of the red blood cells. Likewise, it is possible that such changes are required to guard the pregnant woman against a scenario of increased free radical production (Wisdom et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reports on GSH concentrations during pregnancy are also controversial: some investigators showed an increase (Németh et al 2001;Wisdom et al 1991), whereas others reported a decrease (Arikan et al 2001) or no significant change (Naziroglu et al 2004) during pregnancy. Németh et al (2001) suggested that an increased GSH concentration in pregnant women was an adaptation to maintain the adequate redox milieu of the red blood cells. Likewise, it is possible that such changes are required to guard the pregnant woman against a scenario of increased free radical production (Wisdom et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported an increase of the GSH-Px in pregnancy (Djordjevic et al 2004;Uotila et al 1991), yet others have indicated either no significant change (Arikan et al 2001;Balal et al 2004;Nakai et al 2000;Naziroglu et al 2004) or a reduction (Behne and Wolters 1979). The reports on GSH concentrations during pregnancy are also controversial: some investigators showed an increase (Németh et al 2001;Wisdom et al 1991), whereas others reported a decrease (Arikan et al 2001) or no significant change (Naziroglu et al 2004) during pregnancy. Németh et al (2001) suggested that an increased GSH concentration in pregnant women was an adaptation to maintain the adequate redox milieu of the red blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 In the later process, a normal level of G6PDH is required; this is the key enzyme in the pentose phosphate pathway, as it provides the energy that is needed for GSH synthesis. 22 Our results show a decrease in GSH levels with and increase in GSSG and in GPX and GRX activities in hypertensive groups; this may be the expression of an increased oxidative stress leading to depletion of GSH and the consequent increase in GSSG, that failed to recycle into GSH (even although GPX and GRX were increased as a compensatory mechanism). Probably, a part of the generated GSSG can be reduced back to GSH by the action of GRX, but the rate of GSH oxidation would exceed the rate of GSSG reduction.…”
Section: Discussionmentioning
confidence: 51%
“…Diminished glutathione levels have been found previously in women with preeclampsia and GH. 21,22 Regarding GPX, controversial results have been published; most studies suggest a total enzymatic activity lower in the placenta, whole blood, plasma and even in umbilical venous plasma, although any other studies have found higher levels in whole blood of preeclampsia or in plasma from patients with HELLP syndrome. 3,6,23 The concentration of the specific GPX types (GPX 1-4) may have a role and explain in part these different results.…”
Section: Discussionmentioning
confidence: 99%
“…Many methods were reported to determine GSH and GSSG, one of which accepted as routine is based on the 5,5'-dithio-bis(2-nitrobenzoic acid) (DTNB)-GSSG reductase recycling assay (Nemeth et al, 2001). This method responds to both GSH and GSSG, and GSHt and GSSG must be determined separately.…”
Section: Introductionmentioning
confidence: 99%